The Influence of Fear of AI Replacement and Technology Readiness on Career Adaptability Among Generation Z: The Mediating Role of AI Literacy - Agiya Prameswari; Alma Azzahra; Devi Natassia Irawan (Riviera Publishing, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed the nature of work and created new challenges for Generation Z, particularly regarding career uncertainty, technological disruption, and the need for adaptive competencies. While AI provides opportunities for improving productivity and innovation, concerns about job displacement may influence individuals’ psychological readiness to face future career changes. This study aims to examine the influence of Fear of AI Replacement and Technology Readiness on Career Adaptability among Generation Z, with AI Literacy as a mediating variable. This research employed a quantitative approach using an explanatory research design. Data were collected through an online survey involving 250 Generation Z respondents in Indonesia who had experience using AI-based applications. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that Fear of AI Replacement has a significant negative effect on AI Literacy and Career Adaptability, while Technology Readiness positively affects AI Literacy and Career Adaptability. Furthermore, AI Literacy has a significant positive influence on Career Adaptability and partially mediates the relationships between Fear of AI Replacement, Technology Readiness, and Career Adaptability. These findings highlight that AI Literacy serves as an essential adaptive competency that enables Generation Z to respond effectively to AI-driven workplace transformation. This study concludes that strengthening AI Literacy and technology readiness is crucial for developing a more adaptable and resilient future workforce in the era of artificial intelligence.